Pengelolaan Masalah Pernapasan pada Pasien dengan Heart Decompensation di IGD RSA Universitas Gadjah Mada: Case Report - Noviya Ayuningtyas; Hersinta Retno Martani; Setyawan Setyawan (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2023)
Background: Heart decompensation is a heart failure exacerbation caused by the body’s decompensated mechanism. Uncontrolled hypertension is one of the risk factors for heart decompensation that worse the decompensated mechanism in the presence of target organ damage (TOD). Patient with heart decompensation also suffers dyspnea, ortopnea, and paroxysmal nocturnal dyspnea (PND).Objective: To describe the management of breathing problem in patient with heart decompensation in emergency department (ED).Case: A 39-year-old woman came to ED with severe shortness of breath that has been felt since this week and has gotten worse for past few days. Her condition was as follow saturation 94%, RR 45x/ minutes, HR 153x/minutes, BP 200/125mmHg.Result: Breathing problem management in this patient was helped by oxygen therapy, positioning, mucolytic, bronchodilator, antibiotic, and corticosteroid. Breathing problem was improved after administering the therapy based on effort, frequency, depth in breathing, and oxygen saturation. In addition to breathing problem, circulation problem was also managed comprehensively and had shown improved outcome.Conclusion: Administration of therapy in the ED in heart decompensation patient with breathing problem has improved with increased saturation, reducted shortness of breath, and expelled excess fluid.ABSTRAKLatar belakang: Heart decompensation merupakan faktor yang memperparah kondisi gagal jantung kronis yang disebabkan oleh mekanisme dekompensasi tubuh. Hipertensi tidak terkontrol merupakan salah satu faktor risiko heart decompensation yang dapat memperburuk mekanisme dekompensasi dengan adanya target organ damage (TOD). Pasien dengan heart decompensation juga disertai masalah pernapasan seperti dyspnea, ortopnea, dan paroxysmal nocturnal dyspnea (PND).Tujuan: Mendeskripsikan pengelolaan masalah pernapasan pasien heart decompensation di instalasi gawat darurat (IGD).Laporan kasus: Pasien wanita, berusia 39 tahun, datang ke IGD dengan keluhan sesak napas berat yang dirasakan sejak seminggu ini dan memberat dalam beberapa hari ini. Saturasi 94%, RR 45x/ menit, nadi 153x/menit, TD 200/125mmHg.Hasil: Penatalaksanaan masalah pernapasan pada pasien dengan pemberian terapi oksigen, positioning, mukolitik, bronkodilator, antibiotik, dan kortikosteroid. Masalah pernapasan pada pasien mengalami perbaikan setelah pemberian terapi tersebut. Hal ini dilihat berdasarkan usaha, frekuensi, kedalaman bernapas, dan saturasi oksigen. Selain masalah pernapasan, masalah sirkulasi pada pasien juga dikelola secara komprehensif dan menunjukkan outcome yang membaik.Simpulan: Pemberian terapi di IGD pada pasien heart decompensation dengan masalah pernapasan mengalami perbaikan dengan peningkatan saturasi, sesak napas berkurang, cairan berlebih dapat dikeluarkan.